Applications of BMI or BSI: Differences and Revisions According to Age and Height - Otto W. B. Schult; Ludwig E. Feinendegen; Stephan Zaum; Walton W. Shreeve; Richard N. Pierson (Journal of Obesity)
Validation of body-mass relationships requires a careful statistical analysis of data of normal weight individuals. BMI (ratio between body mass and square of body height) and BSI values (ratio between mass and cube of body height) have been calculated for 99 persons with ages between 1 day and 76 years. These BMI or BSI values have been used for least squares fits yielding mean BMI or BSI values, their variances (providing precision), and average deviations of individual BMI/BSI values from the BMI/BSI means. The latter allows limits to over- and underweight. For adults we found mean values of BSI of 12.36 and confirmed 21.7 for the mean BMI; but the BSI was 1.4 times more precise than the BMI. For children shorter than 1.3 m and younger than 8 years we found the BMI average of 15.9 and over-/underweight limits of 17.4/14.4 being significantly smaller than and incompatible with the recommended BMI values.